"I'm the Empty Stage Where Various Actors Act Out Various Plays" : Theatre Translator's View of their Work - Aaltonen, Sirkku (Federal University of Santa Catarina, 2023)
When theatre translators are commissioned to translate a play, they know the stage it is intended for, the director and sometimes even the actors. In a small country, theatre translation has always been significant, and even today translated plays account for around half of the annual performances on the Finnish stage. This situation has triggered off the following piece of research into how theatre translators themselves see their own role in the preparation of a production and, also, how closely their work follows the one that actors do in constructing characters. The two questions set for the analysis were: 1) what is theatre translators’ experience of their physical participation in the construction of a performance?; and 2) how far does their psychological involvement go into the lives of the play’s characters? I drew my material from two collected works of theatre translators’ self-reflections that I have edited in Finland. Of the two compilations, I selected 27 articles written by theatre translators. My method was Critical Discourse Analysis, and my toolbox consisted of discourse, repertoire, (theme), topic and metaphorical narratives. The analysis revealed repertoires that consisted of the physical participation in the production process that fell mostly in the category of Exclusion or Liminality, and to a much lesser extent to that of Inclusion. The answers to the second question concerning the psychological involvement in the lives of the play’s characters fell mostly in the repertoire which I labelled as the Brechtian Verfremdung, or Distancing and somewhat less to the repertoire of Emotional Recall, or Memory, of the Stanislavski Method.
Keywords: Theatre translators’ self-reflections; Theatre translator in the rehearsal room; Theatre translation as acting; Theatre translation; fi=Viestintätieteet|en=Communication Studies|